ANALYSIS OF THE CLINICAL COURSE OF THE GESTATIONAL PERIOD IN PATIENTS WITH RISK OF FETAL INFECTION - Куса, О. М.; Сніжко, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Reducing morbidity in children born to mothers whose gestational process was complicated by the presence of mixed forms of infectious agents of TORCH-group is an actual problem of modern perinatology. One of the most dangerous and least studied significant perinatal infections is a parvovirus infection; it may have a bad influence on pregnancy leading to fetal pathology, causing development and increasing perinatal loss. So, it is necessary to find informative diagnostic criteria concerning fetal involvement when mother is infected by combined forms of TORCH-pathogens and effective treatment and preventive measures for these women and their babies, causing the need to find approaches to the study of this problem; so, it is a clear rationale for the relevance of the chosen direction. The article describes the clinical course of the gestational period in patients with risk of fetal infection. It has been analysed the peculiarities of the state and development of newborns born to women who are investigated. The new criteria for predicting obstetric and perinatal complications in women with viral, bacterial and mixed infections were proposed. The aim was to reduce the frequency of obstetric and perinatal complications in women with the risk of intrauterine infection by implementing preventive and curative measures at the preconception stage basing on the study of individual indicators of local immunity, acute phase proteins level, and functional state of the fetoplacental complex. The developed and implemented measures of antenatal pregnancy observation and preconception training contributed to the prevention of intrauterine infection, reduced frequency of complications in gestational process and improvement of perinatal outcomes.